Training, competence, and quality improvement in echocardiography: the European Association of Cardiovascular Imaging Recommendations: update 2020. (27th November 2020) - Popescu, Bogdan A; Stefanidis, Alexandros; Fox, Kevin F; Cosyns, Bernard; Delgado, Victoria; Di Salvo, Giovanni Di; Donal, Erwan; Flachskampf, Frank A; Galderisi, Maurizio; Lancellotti, Patrizio; Muraru, Denisa; Sade, Leyla Elif; et al.
Abstract: The primary mission of the European Association of Cardiovascular Imaging (EACVI) is 'to promote excellence in clinical diagnosis, research, technical development, and education in cardiovascular imaging'. Echocardiography is a key component in the evaluation of patients with known or suspected cardiovascular disease and is essential for the high quality and effective practice of clinical cardiology. The EACVI aims to update the previously published recommendations for training, competence, and quality improvement in echocardiography since these activities are increasingly recognized by patients, physicians, and payers. The purpose of this document is to provide the general requirements for training and competence in echocardiography, to outline the principles of quality evaluation, and to recommend a set of measures for improvement, with the ultimate goal of raising the standards of echocardiographic practice. Moreover, the document aims to provide specific guidance for advanced echo techniques, which have dramatically evolved since the previous publication in 2009.